Preparação e caracterização de vidros e vitrocerâmicas fluorofosfatos no sistema ternário NaPO3-WO3-PbF2 - Braz, Celso Eduardo (2014)
The main goal of this work has been the synthesis of tungstate phosphate glasses based on sodium polyphosphate NaPO3 and tungsten oxide WO3 with increasing amounts of lead fluoride PbF2 and doped with rare earth ions in order of obtaining new glass compositions for optical applications. The investigated ternary system has been NaPO3-WO3-PbF2 with WO3 being used as a glass intermediary for higher chemical and termal stabilities. Firstly, glass compositions were investigated in the binary system (100-x)NaPO3-xWO3 with x=20, 30 and 40% in order to define the best NaPO3/WO3 ratio for further PbF2 incorporation. The molar ratio 60NaPO3-40WO3 has been identified as the best precursor glass for lead fluoride incorporation. Glass samples were obtained by the melt-quenching method in the ternary system NaPO3-WO3-PbF2 with PbF2 concentration varying from 0 to 60 mol% and a fixed NaPO3/WO3 molar ratio of 3/2. Synthesis conditions such as melting time and melting temperature were improved for the formation of transparent, homogeneous and stable glasses with low fluorine loss during the melting process. Two series of rare earth doped glasses were then prepared: the first series has been synthesized with 0,2% Er3+, 1% Yb3+ and increasing amounts of PbF2 in order to investigate the luminescent behavior of Er3+ in function of PbF2 concentration. The second series has been prepared with 0,2% Eu3+ and increasing amounts of PbF2 with the aim to use the Eu3+ luminescence as a structural probe. These glasses were characterized by DSC in order to determine the termal behavior in function of composition. Structural investigations were also performed by Raman scattering and allowed to identify the modifier behavior of PbF2 in the covalent network with a progressive break of the covalent bridging bonds. A crystallization study performed on the most PbF2 concentrated glass samples (40%, 50% and 60%) identified a preferential precipitation of lead fluorophosphate Pb5F(PO4)3 for samples containing 40% and 50% of PbF2 with a dominant volume crystallization mechanism while sample containing 60% of PbF2 exhibited precipitation of cubic ß-PbF2 with a dominant volume crystallization. UV-Vis absorption spectra obtained on Er3+/Yb3+ codoped glass samples allowed to identify absorption bands due to f-f electronic transitions and the absorption bands related with the dark color of less PbF2 concentrated glass samples. Emission spectra of Eu3+ doped glasses in the visible range pointed out changes in the intensity ratio between electronic transitions 5D0?7F2 and 5D0?7F1, related with structural changes in the Eu3+ neighborhood with a symmetry increase with increasing PbF2 content, probably related with progressive coordination of Eu3+ with F-. Finally, excitation and emission spectra of Er3+/Yb3+ codoped glass samples also pointed out important changes in the luminescent properties in function of PbF2 concentration related with structural changes around rare earth ions as well as a higher energy transfer efficiency between Er3+ and Yb3+ ions with increasing PbF2 contents